Implementation of strategic planning as an organizational human resources management process - Paroli Paroli (Jurnal Ekonomi, 2024)
Strategic planning is a systematic approach that can help organizations identify long-term goals and develop strategies to achieve them. This research aims to investigate and analyze the application of strategic planning in the context of human resource management (HR) in organizations. This research uses a qualitative approach with descriptive methods. The research results show that the application of Strategic Planning in human resource (HR) management has a positive impact on achieving organizational goals. Strategic planning steps, from mission identification to performance evaluation, are proven to form a solid foundation for effective HR management. The results include increased employee motivation and engagement, optimized use of human resources, and organizational adaptability to environmental changes. Additionally, a continuous performance evaluation system helps identify areas of improvement and improvement, creating a responsive and efficient work environment. Overall, this research supports the importance of integrating Strategic Planning in HR management strategies to achieve organizational sustainability and success.